Predicting Post Traumatic Growth Based upon Self-Efficacy and Perceived Social Support in Cancer Patients - Lotfi-Kashani, Farah (Cancer Research Center, Shahid Beheshti University of Medical Sciences, 2014)
BACKGROUND: Despite the fact that being exposed to traumatic and stressful events could have severe consequences, studies have shown that even in the wake of negative events such as cancer diagnosis, we see some changes and positive impacts in scheme, philosophy of life and self-perception, a process which is called Post Traumatic Growth (PTG). The aim of the current research is to define share of self-efficacy and perceived social support in the prediction of PTG. METHODS: The research is a correlation type. For this aim, 95 patients with cancer came to Shohadaye Tajrish Hospital, Tehran, Vali-e-Asr Hospital, Zanjan, and Mehraneh Charity Institute, Zanjan in 2012 have been selec ted based on available sampling and evaluated regarding self-efficacy, and perceived social support and PTG. RESULTS: Data analysis using Pearson correlation and regression analysis (simple and multiple) showed that self-efficacy and Perceived Social Support in cancer patients have direct significant relation with variable of PTG and explain 13.5%, 10.6% and jointly 20.7% of PTG changes respectively. CONCLUSION: The research findings show that the variables of self-efficacy and Perceived Social Support explain significantly the PTG and these psychological variables can be used to provide improvement plans and mental health and PTG facilities.